Iminosugar‐Cyclopeptoid Conjugates Raise Multivalent Effect in Glycosidase Inhibition at Unprecedented High Levels. Issue 15 (24th February 2016) - Lepage, Mathieu L.; Schneider, Jérémy P.; Bodlenner, Anne; Meli, Alessandra; De Riccardis, Francesco; Schmitt, Marjorie; Tarnus, Céline; Nguyen‐Huynh, Nha‐Thi; Francois, Yannis‐Nicolas; Leize‐Wagner, Emmanuelle; Birck, Catherine; Cousido‐Siah, Alexandra; et al.
Abstract: A series of cyclopeptoid‐based iminosugar clusters has been evaluated to finely probe the ligand content‐dependent increase in α‐mannosidase inhibition. This study led to the largest binding enhancement ever reported for an enzyme inhibitor (up to 4700‐fold on a valency‐corrected basis), which represents a substantial advance over the multivalent glycosidase inhibitors previously reported. Electron microscopy imaging and analytical data support, for the best multivalent effects, the formation of a strong chelate complex in which two mannosidase molecules are cross‐linked by one inhibitor. Abstract : Breaking sweet records ! Cyclopeptoid‐based iminosugar clusters (see figure) show the largest multivalent effects ever reported in glycosidase inhibition (up to 4700‐fold on a valency‐corrected basis). Electron microscopy imaging and analytical data support the formation of sandwich‐type complexes in which two mannosidase molecules are cross‐linked by one inhibitor.